The Use of Multisensorial Media in Learning Writing Narration Based on Balance of Brain Functions in Elementary Schools - Ririen Wardiani; Sarwiji Suwandi; Andayani Andayani; Budiyono Budiyono (STKIP Singkawang, 2019)
The purpose of this study is to describe the application of the use of multisensory media in learning to write narratives based on balancing brain function. The research method used is descriptive method with a qualitative approach. Place of research in elementary schools in Ponorogo. Subjects in the study were teachers and elementary school students in grade IV. Data collection techniques are direct observation techniques, interview techniques, and tests. The instruments of data collection are observation guides, interview guides, and test questions. The data analysis technique uses mastery learning guidelines. The results showed that the use of multisensory media in the form of media images, concrete objects, and film media can be used to ignite emotions as a basis for the initial search and development of ideas. The use of picture media can produce students categorically mastery as many as 30 students, the use of concrete media objects 59 students, and the use of film media as many as 63 of the 72 students studied. The use of multisensory media is very important in implementing learning based on balancing brain function.